Peripheral cytokine levels in patients with idiopathic parkinson's disease undergoing subthalamic nucleus deep brain stimulation - Kocabicak, Ersoy; Sen, Sedat; Uzun, Hafize; Ozturk, Sait; Yildiz, Mustafa Onur; Tuzun, Erdem; Temel, Yasin (Nature Portfolio, 2025)
Parkinson's disease (PD) is a movement disorder caused by dopaminergic neuron degeneration. In addition to L-DOPA and agonists, deep-brain stimulation (DBS) is also used in appropriate patients in the middle and advanced stages. The most common target for DBS is the subthalamic nucleus (STN). STN stimulation results in significant improvement in the clinical manifestations of the disease. In addition to its ameliorating effect on well-known clinical findings, stimulation has secondary effects that are not sufficiently known. This study aims to investigate the effects of STN-DBS on peripheral pro-inflammatory and anti-inflammatory cytokine levels in patients with idiopathic PD, and to explore whether changes in these biomarkers correlate with clinical improvements following DBS. The study included 32 patients with idiopathic PD who underwent STN-DBS at Neurosurgery Clinics. The mean Unified Parkinson's Disease Rating Scale (UPDRS) motor score improved from 45.71 (preoperative, Med OFF) to 17.90 (postoperative, STIM ON / Med OFF) and to 13.10 (6 months after surgery), corresponding to 60.8% and 71.3% improvements, respectively. LEDD decreased significantly over time (p < 0.001), and BDI scores improved significantly postoperatively. MMSE scores increased progressively at each follow-up. Medical treatment ameliorated the effect on UPDRS score by 49.1% in the preoperative period. However, no statistically significant changes were observed in serum cytokine levels (IL-1 beta, IL-6, IL-10, TNF-alpha) across the study period. No correlations were found between cytokine levels and clinical variables. STN-DBS is an effective and safe treatment for improving motor symptoms in patients with idiopathic PD, and it may also contribute to a reduced need for medication and gradual cognitive improvement. However, peripheral cytokine levels (IL-1 beta, IL-6, IL-10, and TNF-alpha) remained unchanged, suggesting that the clinical benefits of STN-DBS are unlikely to be mediated directly through peripheral immune modulation. Nevertheless, more complex immunological mechanisms cannot be excluded. Further studies with larger cohorts and longer follow-up are warranted to clarify these potential effects.
Keywords: Parkinson's disease; Subthalamic nucleus; Deep brain stimulation; Neuroinflammation; Cytokine; IL-1beta; IL-6; TNF-alpha